CASE SERIES OF SEVERE INSULIN RESISTANCE IN HOSPITALIZED PATIENTS - WH, Wan Mohd Hafez; Yahaya, Norhayati; Roslan, Teh Roseleen Nadia; MA, Masliza Hanuni (Journal of the ASEAN Federation of Endocrine Societies, 2023)
INTRODUCTION/BACKGROUND Hyperglycaemia is common in hospitalized patients and is associated with poorer clinical outcomes. Multiple factors contribute to hyperglycaemia in hospitalized patients, such as underlying medical conditions, pathophysiological stress and medications. The development of transient insulin resistance is a known cause of hyperglycaemia in patients with and without diabetes, but we rarely see severe cases. Here we report 2 cases of severe insulin resistance in hospitalized patients to illustrate the challenge of managing these cases. CASE The first case is a 34-year-old male with type 2 diabetes mellitus, morbid obesity (BMI 44 kg/m2), hypertension, hyperlipidaemia and right knee arthrofibrosis. He developed severe diabetic ketoacidosis with severe insulin resistance secondary to severe pneumonia, steroid therapy and morbid obesity five days after knee surgery. The second case is a 57-year-old female with type 2 diabetes mellitus and obesity (BMI 33 kg/m2) who developed severe insulin resistance secondary to severe pneumonia. Both cases were treated in an intensive care unit (ICU) with high-dose insulin infusion of up to 47 units/hour and guided by Nebraska Medical Centre insulin protocol. There were good outcomes for both patients, and insulin resistance resolved after treatment of sepsis. CONCLUSION Severe insulin resistance in hospitalized patients is a challenging condition to treat. Besides using high doses of insulin, we also need to treat the underlying medical condition which can precipitate insulin resistance.